1993
DOI: 10.1104/pp.103.2.421
|View full text |Cite
|
Sign up to set email alerts
|

A Model of the Regulation of Nitrogenase Electron Allocation in Legume Nodules (I. The Diffusion Barrier and H2 Inhibition of N2 Fixation)

Abstract: A mathematical model is presented to explain the regulation of nitrogenase electron allocation to N, fixation (FAC) in legume nodules. l h e model is based on two assumptions: (a) that Hz inhibits Nz fixation in a competitive manner; and (b) that O,, H,, and N, move into and out of nodules by diffusion and their movement is impeded by a diffusion barrier, the permeability of which is controlled to maintain a very low infeded cell O, concentration. When the model was used to simulate nodules displaying a range … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

1994
1994
2017
2017

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(2 citation statements)
references
References 28 publications
0
2
0
Order By: Relevance
“…AI1 these mechanisms are based on the fact that solubility and diffusion of 0 2 in an aqueous liquid phase are much lower than in a gas phase. Mathematical models of gas diffusion in nodules (Sheehy et al, 1985(Sheehy et al, , 1987Sheehy and Bergersen, 1986;Hunt et al, 1988;Denison, 1992;Moloney and Layzell, 1993) are consistent with the presence of a variable bamer in the cortex, which functions to maintain an extremely low O2 concentration throughout the entire central infected zone of the nodule.…”
mentioning
confidence: 90%
“…AI1 these mechanisms are based on the fact that solubility and diffusion of 0 2 in an aqueous liquid phase are much lower than in a gas phase. Mathematical models of gas diffusion in nodules (Sheehy et al, 1985(Sheehy et al, , 1987Sheehy and Bergersen, 1986;Hunt et al, 1988;Denison, 1992;Moloney and Layzell, 1993) are consistent with the presence of a variable bamer in the cortex, which functions to maintain an extremely low O2 concentration throughout the entire central infected zone of the nodule.…”
mentioning
confidence: 90%
“…This difference was consistent with the results of previous studies (Sung et al 1991, Diaz del Castillo et al 1992) which have reported a small decline in EAC in nodules in which TNA has been inhibited. Moloney and Layzell (1993) have provided evidence that the EAC shift is a consequence of a greater banier to O2, H2 and N2 diffusion that results in more competitive inhibition of N2 fixation by Hj, gas within the infected cells.…”
Section: Experiments 2: Nitrogenase Activity In Maple Arrow and K466mentioning
confidence: 99%